Spectroscopic Study of the Metallation Reactions of Bis(dialkylamino)- 4-methyl-and 2,4-dimethyl-2,4-pentadienylboranes - Shneine, Jawad K (Al-Nahrain Journal of Science, 2013)
Metalation Reactions of 2,4-dimethyl-and 4-methyl-2,4-pentadienylboranes, prepared from the reaction of potassium-2-methyl- and 2,4-dimethyl-1,3-pentadienide with chlorobis (dialkylamino) borane (R=Me, Et), were investigated. Lithiumdiethylamide LiNEt2 in THF was used as base to achieve metalation. Li(TMEDA*)-1-dimethylamino-3-methylboratabenzene and bora-2,4- and bora-2,5-cyclohexadiene were obtained from bis(dialkylamino)-4-methyl-2,4-pentadienylborane in moderate and good yields. Mass, 11B, 1H, 13C NMR spectroscopy were used to characterize the intermediates and products. Steric effects found to have dominating and controlling role on the results.